2003
DOI: 10.1179/cim.2003.4.2.96
|View full text |Cite
|
Sign up to set email alerts
|

How We Do It: Using a surgical navigation system in the management of the ossified cochlea

Abstract: The ossified cochlea poses both concerns and challenges to any implant team. One of the surgical aims is to implant as many of an implant system's electrodes into the cochlea as close to the modiolus as possible, thus facilitating stimulation of the surviving cell bodies in the spiral ganglion. Within the field of otorhinolaryngology various surgical navigation systems have been introduced to facilitate surgical orientation during endoscopic sinus and skull-base surgery. The principle behind such systems is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…8 Similar to the presented case, they performed a two-tunnel cochlear drill-out procedure and implanted a split array. Using the Medtronic Xomed LandmarX system (Medtronic-Xomed, Jacksonville, FL), a surgical drill was fitted with a small infrared emitting diode and registered to a reference head frame.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…8 Similar to the presented case, they performed a two-tunnel cochlear drill-out procedure and implanted a split array. Using the Medtronic Xomed LandmarX system (Medtronic-Xomed, Jacksonville, FL), a surgical drill was fitted with a small infrared emitting diode and registered to a reference head frame.…”
Section: Discussionmentioning
confidence: 75%
“…Such constrained linear drilling may be particularly useful in navigating the ossified cochlea given restricted access through the facial recess corridor, close proximity to vital structures including the facial nerve, modiolus, and internal carotid artery and obscured surgical landmarks from neossofication. 8 We report use of such a system for cochlear drill-out in a patient with complete cochlear ossification. Proximal and distal basal turn access permitted full split array electrode insertion after an unsuccessful attempt was made on the contralateral side using conventional technique.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, the imaging protocol specifies CBCT image acquisition with a radiation dose of 0.35 mSv per scan, with up to four to six intraoperative image updates over the course of a procedure such that the accumulated dose is less than a typical diagnostic CT scan (2)(3)(4)(5). 16 Due to the half-circular (approximately 178 ) orbit of the C-arm gantry, in which the xray tube travels below the table and only posterior to the head, the dose to radiosensitive structures (e.g., the eyes) may be considerably lower for cone beam imaging than for conventional diagnostic CT using a full 360 orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Raine et al [17] reported the use of an IGS system for a customized cochlear implant placement in a patient with an abnormally ossified inner ear. Caversaccio et al [18] recently reported on the use of IGS systems in repairing aural atresia, a condition in which the ear canal does not properly develop.…”
Section: Discussionmentioning
confidence: 99%